GURU SEBAGAI AGEN INOVATOR BERBASIS HIGHER ORDER THINKING SKILLS - I Putu Suardipa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The role of the teacher in educational innovation involves the teacher’s open andsensitive attitude towards change or innovation and its role as an agent of renewal as well as anadapter, in educational innovation. Teachers as instructors emphasize more on the task ofplanning, carrying out the teaching and learning process and assessing the results. New ideas(innovations) conducted by the teacher should aim to improve teaching and learning activitiesthrough the skills of Higher Order Thinking Skills. High-level thinking requires a variety ofdifferent learning and teaching steps by merely learning facts and concepts. In high-level thinkingincludes learning activities towards the skills in deciding complex things such as critical thinkingand thinking in solving problems. Even though high-level thinking is difficult to learn and teach,its usefulness is no doubt.Keywords: Innovative teacher, Higher Order Thinking Skills